A generalized analytical model for sloped rolling-type seismic isolators. (1st May 2017) - Wang, Shiang-Jung; Yu, Chung-Han; Lin, Wang-Chuen; Hwang, Jenn-Shin; Chang, Kuo-Chun
Highlights: A generalized analytical model for sloped rolling-type seismic isolators. Experimental verification for the proposed analytical model. Vertical excitation significantly affects horizontal acceleration performance. Abstract: The exact and simplified generalized analytical models for the sloped rolling-type seismic isolator in which two V-shaped surfaces in contact with cylindrical rollers are designed with arbitrary sloping angles are proposed. Numerical predictions are compared with horizontal seismic simulation test results to demonstrate the accuracy and practicability of the proposed simplified model. Furthermore, the influences arising from two simplification assumptions on the horizontal acceleration prediction are numerically examined. The results indicate that the effect of vertical acceleration excitation plays a more crucial role in prediction accuracy and conservative design compared to that of higher order terms of sloping angles.